Pengaruh Kepercayaan, Kemudahan dan Pendapatan Terhadap Keputusan Pembelian Menggunakan Metode Pinjaman Online SpayLater ( Studi Kasus Mahasiswa di Kota Malang) - Anggraini, Tasya Meylina Ari; Mardani, Ronny Malavia; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to find out more about trust, convenience and income regarding purchasing decisions using the SpayLater online loan method. This type of research is explanatory research with a quantitative approach. The data source used in this research is primary data and the population of this research is students in Malang City. The sampling technique uses a purposive sampling method and data collection techniques using a questionnaire using a Likert scale model and analyzed using linear multiple regression through the Statistical Program Social Science (SPSS). The results of this research show that Trust, Convenience and Income simultaneously influence Purchase Decisions Using the SpayLater Online Loan Method. Keyword : Trust, Convenience, Income, Purchase Decisions, Online Loans, SpayLater